2020
DOI: 10.1111/jocd.13641
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of nano‐microneedle‐assisted phenylethyl resorcinol for the treatment of infraorbital dark circles

Abstract: Infraorbital dark circles are defined as a symptom that presents darkness under infraorbital eyelids. Throughout cultures, social views are similar, in that infraorbital dark circles contribute to a tired, aging, and even sad looks. 1 It is reported that a woman in the United States spends an average of $15 000 on cosmeceuticals in her lifetime, of which under-eye concealers were the majority, 2 reflecting people's great concern about periocular problems. Possible etiologic factors of the dark circles include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Utilizing this method, drug penetration can be increased by up to 10 or 20 times. 11,12,18 However, it should be noted that the rate of "local irritation from medication" of group A was higher than that of group B, which might be related to the application of nano-microneedles.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Utilizing this method, drug penetration can be increased by up to 10 or 20 times. 11,12,18 However, it should be noted that the rate of "local irritation from medication" of group A was higher than that of group B, which might be related to the application of nano-microneedles.…”
Section: Discussionmentioning
confidence: 90%
“…Nano-microneedle technology has emerged in recent years to promote the penetration of drugs into the skin. 11,12 It has the advantages of safety, convenience, rapidity, and painlessness, which had been used in clinical practice. This study will review and report the clinical application effects and adverse reactions of the three methods: introduction of timolol maleate with nano-microneedles, application of timolol maleate, and oral propranolol.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter of each needle is only 80 nm, which is almost noninvasive. Utilizing this method, drug penetration can be increased by up to 10 or 20 times [11,12,18]. However, it should be noted that the rate of "Local irritation from medication" of Group NM was higher than Group MS, which might be related to the application of nano-microneedles.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used for the delivery of drugs and other substances between cells because of their small diameter. The study found that the nano-microneedles can exert their effects while minimizing the damage to the intracellular environment [11,12]. The nano-microneedle has the advantages of safety, convenience, rapidity, and painlessness which had been used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Neither invasive nor non-invasive therapies can provide effective treatment yet; consequently, the satisfaction and cure of patients are not satisfied. Therefore, new approaches and finding new medications for IOD are appreciated [7,8]. Traditional medicines and natural products have been proposed as possible sources of novel pharmaceuticals [9,10].…”
Section: Introductionmentioning
confidence: 99%